(untitled) - Bleier, Carol Stein (Pittsburgh, 1997)
Almost 100 years ago, a small group of Pittsburgh's Jewish immigrant women stood up and declared their intention to secure a place for poor, sickly Jews to die in peace and comportl for Jewish medical students to learn and Jewish physicians to practice their profession, and for the Jewish community, and all others-regardless of race, religion or creed - to receive the finest medical care.
Keywords: Bệnh viện,Hospitals; Pennsylvania,Pennsylvania